2011
DOI: 10.1039/c0dt01036g
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and computational characterization of CuII–OOR (R = H or cumyl) complexes bearing a Me6-tren ligand

Abstract: A copper(II)–hydroperoxo complex, [Cu(Me6-tren)(OOH)]+ (2), and a copper(II)–cumylperoxo complex, [Cu(Me6-tren)(OOC(CH3)2Ph)]+ (3), were synthesized by reacting [Cu(Me6-tren)(CH3CN)]2+ (1) with H2O2 and cumyl-OOH, respectively, in the presence of triethylamine. These intermediates, 2 and 3, were successfully characterized by various physicochemical methods such as UV-vis, ESI-MS, resonance Raman and EPR spectroscopies, leading us to propose structures of the Cu(II)–OOR species with a trigonal-bipyramidal geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 73 publications
7
40
0
Order By: Relevance
“…This hypothesis is in agreement with past computational studies 45,19 that have indicated that H-atom abstraction by a Cu II -OOH species is an unfavorable process. However, Poater and Cavallo have suggested that the distal oxygen of the Cu II –OOH species, supported by the related tripodal tetradentate N 4 TMG 3 tren ligand, directly abstracts a H-atom from the guanidinium methyl group (ΔG ‡ = 22 kcal/mol).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This hypothesis is in agreement with past computational studies 45,19 that have indicated that H-atom abstraction by a Cu II -OOH species is an unfavorable process. However, Poater and Cavallo have suggested that the distal oxygen of the Cu II –OOH species, supported by the related tripodal tetradentate N 4 TMG 3 tren ligand, directly abstracts a H-atom from the guanidinium methyl group (ΔG ‡ = 22 kcal/mol).…”
Section: Resultssupporting
confidence: 93%
“…Such procedures are very common, 6,10,11b,11c,19b,29 but as seen here, the presence of additional H 2 O 2 may complicate matters and allow for unintentional reaction pathways or mechanisms.…”
Section: Resultsmentioning
confidence: 94%
“…Based on the analogy of the resonance Raman features with those of reported Cu II -alkylperoxide complexes, [8][9][10][11] a similar type of alkylperoxide complex may be generated in the present reaction. Thus, the band at 831 cm -1 is assigned to the O-O stretching vibrations, whereas the band at 604 cm -1 is due to the Cu-O stretching vibration.…”
Section: Introductionmentioning
confidence: 86%
“…However, we found a recent case where the chemistry appears to proceed through Cu–O homolytic cleavage of Cu II – OOH and subsequent site-specific Fenton chemistry derived from the Cu(I) thus produced reacting with the excess H 2 O 2 present [58]. In general, Cu II -OOH ( Hp ) appear experimentally [55,59] and computationally [60] to not be effective oxidants toward C–H HAT.…”
Section: Primary Cui/o2 Adducts and Reactivitymentioning
confidence: 99%